Early diagnosis of primary melanoma of caecum. Case report and review of the literature - D'Orazio, Beatrice; Bonventre, Sebastiano; Cudia, Bianca; Di Vita, Gaetano; Geraci, Girolamo (Acta Biomedica Atenei Parmensis, 2021)
Malignant gastrointestinal melanoma is usually a metastatic lesion. We report the case of a 79-year-old female asymptomatic patient. Colonoscopy revealed one plane 15 mm pigmented lesion in the caecum. Neither CT scan of the abdomen nor right hemicolectomy revealed no metastatic disease. Histopathological examination of the surgical specimen was indicative of malignant melanoma.A set of additional enquires such as laboratory and imaging tests did not point out any suspicious lesions in the skin, eye, leptomeninges or other sites. Therefore, we made the diagnosis of primary colonic melanoma.The diagnosis of this disease is still a challange and often demanding for a multidisciplinary approach, involving the surgeon, onclogist and even immunotherapy or radiotherapy.